2007
DOI: 10.3132/pcrj.2007.00064
|View full text |Cite
|
Sign up to set email alerts
|

Are we failing workers with symptoms suggestive of occupational asthma?

Abstract: Aims: To assess the route to secondary care for patients with possible occupational asthma, and to document the duration of workrelated symptoms and referral times.Methods: Consecutive patients with suspected occupational asthma were recruited to a case series from six secondary care clinics with an interest in occupational asthma. Semi-structured interviews were performed and hospital case notes were reviewed to summarise relevant investigations and diagnosis.Results: 97 patients were recruited, with a mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 18 publications
0
28
1
Order By: Relevance
“…The paper by Fishwick et al in this issue is therefore a challenge to all of us who work in primary care. 8 Ninetyseven consecutive patients from six secondary care centres with a special interest in occupational asthma were recruited into the study. 96% had consulted their GP at least once with work-related respiratory symptoms.…”
Section: O P Y R I G H T G E N E R a L P R A C T I C E A I R W A Y mentioning
confidence: 99%
“…The paper by Fishwick et al in this issue is therefore a challenge to all of us who work in primary care. 8 Ninetyseven consecutive patients from six secondary care centres with a special interest in occupational asthma were recruited into the study. 96% had consulted their GP at least once with work-related respiratory symptoms.…”
Section: O P Y R I G H T G E N E R a L P R A C T I C E A I R W A Y mentioning
confidence: 99%
“…Systematic research on incidence rates, health impact and socioeconomic burden of occupational asthma is sparse and national estimates are difficult to compare [5][6][7]. Work-related asthma imposes a significant financial cost that is mainly borne by affected employees and government [8,9]. On top of physical impairment, the patient faces problems regarding employment [10] and other psychosocial problems [11].…”
mentioning
confidence: 99%
“…When studying the delaying factors in the diagnostic course [9,[33][34][35], starting symptomatic asthma therapy without being aware of the causal link with occupational exposure is one of the main reasons of delay [36,37]. In this respect, the availability of effective medication for the control of asthma often results in the fact that physicians do not sufficiently look for an occupational (or other) aetiology in their asthmatic patients!…”
mentioning
confidence: 99%
“…[9][10][11][12] Studies from a range of countries, however, have identified average delays of several years in the patient journey for symptomatic workers, which in part relate to the condition being under-recognised in primary care. [13][14][15][16] National published guidelines for the prevention, The full version of this paper, with online Appendix, is available at www.thepcrj.org …”
Section: Introductionmentioning
confidence: 99%
“…PRIMARY CARE RESPIRATORY JOURNAL www.thepcrj.org [13][14][15][16] which may in part relate to deficiencies in undergraduate and postgraduate occupational training. This is highly relevant for affected workers, since early and accurate diagnosis linked with exposure modification offers the best prognosis, both for health and socioeconomic outcomes.…”
mentioning
confidence: 99%